Conversion - Howe, Katherine, 1977- (G. P. Putnam's Sons, an imprint of Penguin Group (USA), 2014)
When girls start experiencing strange tics and other mysterious symptoms at Colleen's high school, her small town of Danvers, Massachusetts, falls victim to rumors that lead to full-blown panic, and only Colleen connects their fate to the ill-fated Salem Village, where another group of girls suffered from a similarly bizarre epidemic three centuries ago.